Vienna, the Spanish Ambassador and the Nuncio: The 3rd Marquis of Aytona and the Fading Catholic Alliance (1624–1629) (Theatrum historiae, 2019)
The papacy and the Spanish Monarchy were, by the decade of 1620, the most global powers in Europe and their dynastic and confessional priorities led to changing clashes and alliances around the world. Local contexts were decisive: in Rome, the creation of the Congregation of Propaganda Fide challenged Spanish control over missionaries beyond Europe, while in Madrid the royal favourite Olivares attempted to establish a major Catholic alliance with France and the papacy against the Protestants. In Vienna, the conflict between papal and Spanish diplomats was hard to dissimulate after 1623. The arrival of a new ambassador –the 3rd Marquis of Aytona– supposedly closer to the papacy, should reverse this situation. This article explores the causes of the distancing between two intrinsic allies. It examines their competing tactics of negotiation and communicative devices to voice their positions at the Imperial court, especially in the polarizing context of the War of the Mantuan Succession.
Keywords: House of Austria; diplomacy; papacy; Thirty Years’ War